From the great recession to the COVID-19 pandemic: The risk of expansionary monetary policies - Miguel Ángel Echarte Fernández; Sergio Luis Ná\~nez Alonso; Ricardo Reier Forradellas; Javier Jorge-Vázquez (Risks, 2022)
Central banks have been pursuing an expansionary monetary policy since before the pandemic, although the health and economic crisis of COVID-19 has boosted asset purchase programmes. After the Great Recession, a new phase began, characterised by low interest rates and liquidity injections. These policies spilled over into financial markets and are leading to higher inflation. These policies stabilised the situation in the short term, but if they continue indefinitely there is a risk of debt overhang, investment mistakes and high inflation in the future. The aim of this article is to analyse monetary policy developments from the Great Recession to the COVID-19 crisis. Correlations between different macroeconomic variables will be shown through IBM SPSS Statistics. For this purpose, bi-variate correlations were used. For the predictions and confidence of the model data, Tableau Desktop Edition was used, which in turn was used for the generation of the graphs. There is a strong correlation between the growth of monetary aggregates and public debt and stock market capitalisation for the selected indicators. The main contribution of this research is the analysis of the long-term effects of a monetary policy.
Keywords: 330; expansionary policy; monetary stimulus; negative interest rates; centralized virtual currencies; balance sheet expansion